EXCHANGE RATE VOLATILITY: AN EMPIRICAL STUDY FOR STATE OF KUWAIT - K. Lawler; S. Sadiq (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка, 2018)

(untitled)
As an oil exporting nation Kuwait suffers from the well-known issue called the Resource Curse given the high reliance on oil revenues for economic growth and development. Traditionally research on small open economies such as Kuwait focus on versions of the Solow Harrod Domar growth models which are predominantly closed models which focus on exogenous growth issues such as saving ratios and the Solow Residual. For an open economy without core problems on capital accumulation, such as Kuwait, it is interesting to disentangle exchange rate volatility issues from key open economy fundamentals such as GDP growth, trade openness, inward foreign investment and exchange rate issues. The purpose of this study is to empirically examine the impact of gross domestic product, trade openness and foreign direct investment on the exchange rate volatility of Kuwait. We have used several advanced statistical tools to better estimate different kinds of relationships. Results show that all factors are significant in determining exchange rate volatility.